2010
DOI: 10.1007/s12029-010-9149-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Expression of Cell Adhesion Molecule Markers (E-Cadherin and Syndecan-1) between Young and Older Age Patients with Gastric Carcinoma

Abstract: Gastric carcinoma in young and old age adults showed no significant difference in respect of the expression of cell adhesion molecule markers. Our result shows that young age alone cannot be predictive of more metastasis and invasion potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It has been shown that the diffuse type of gastric cancer was more prevalent in younger than in older patients [ 5 , 7 , 36 38 ]. In this study, age under 45 years old was significantly associated with diffuse gastric cancer even when adjusting for gender, tobacco smoking, alcohol consumption and family history of gastric cancer in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the diffuse type of gastric cancer was more prevalent in younger than in older patients [ 5 , 7 , 36 38 ]. In this study, age under 45 years old was significantly associated with diffuse gastric cancer even when adjusting for gender, tobacco smoking, alcohol consumption and family history of gastric cancer in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A Mexican study found that polymorphisms of E-cadherin gene was associated with diffuse gastric cancer in young patients [ 37 ]. Furthermore, a study from Korea showed that diffuse GC in young patients had higher proportion of CDH1 alterations and was associated with shorter survival, suggesting that this may contribute to more aggressive clinical course of in young GC patients [ 8 ].Conversely, a study from Iran, did not find any differences in the expression of E-cadherin and Syndecan-1, cell adhesion molecules [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated that the loss of E-CAD expression is associated with a loss of cellular differentiation and increased cellular invasiveness, and it may correlate with muscle involvement and tumor recurrence [20]. Loss of E-CAD is also described in plasmacytoid bladder carcinoma [21], and in other 2 tumor types with aggressive feature, such as diffuse-type gastric cancer and lobular carcinoma of the breast [22,23]. Our data confirm the negative staining of E-CAD in the tumor cells of all the cases, whereas we observed that the dysplastic superficial urothelium strongly expressed E-CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of the expression of Sdc1 and its distribution and localization and association with established prognostic factors and prognostic value have been tested so far in pancreatic cancer [ 14 , 15 ], stomach cancer [ 16 – 18 ], colon cancer [ 19 , 20 ], liver cancer [ 21 ], prostate cancer [ 22 24 ], lung cancer [ 25 28 ], endometrial cancer [ 29 , 30 ], ovarian cancer [ 31 ], squamous head and neck cancer [ 32 36 ], melanoma [ 37 ], laryngeal cancer [ 38 ], cervical cancer [ 39 ], urothelial carcinoma of the bladder [ 40 ], multiple myeloma [ 5 , 41 43 ], and breast cancer [ 44 46 ] where its overexpression generally means a poor prognosis, although various studies have shown conflicting results.…”
Section: Introductionmentioning
confidence: 99%